AN ARCHITECTURE DESIGN FOR SMART E-WASTE MANAGEMENT SYSTEM - Mohd Norikhmal Hishyam Makimin; Raihah Aminuddin; Siti Feirusz Ahamd Fesol (Journal of Islamic, Social, Economics and Development, 2023)
E-waste is an uncommon topic to be discussed nowadays due to the need for more awareness regarding this topic among people. Although there are already several establishments of e-waste collection centers, there still needs to be more awareness among the public on proper e-waste handling. Based on this urgency, this study aims to propose a model of an architecture design for designing a Smart E-waste Management System using the Haversine algorithm. This system will work as a medium to disseminate information, create awareness, and educate the public about e-waste and how it would bring harm to humans and the environment if not handled properly. The proposed model was further implemented with the development of a mobile application software called E-Waste System (EWS). This system consists of two types of users: user (the public) and admin. EWS also featured a geolocation function that allows the users to locate any e-waste location nearby them. This function will assist the users in dropping their e-waste in any associated e-waste location to receive points depending on the category of the e-waste. The results of this study present the use case, flowchart, and the final interface of the proposed system. In the future, the proposed system can be improved in terms of the accuracy of the location markers and able to provide real-time updates based on location-based data.